Où va la vidéo? - Fargier, Jean-Paul; Bellour, Raymond; Chion, Michel; Daney, Serge; Dercon, Chris; Fagone, Vittorio; Lalanne, Dorothée; Virilio, Paul (Paris : Editions de l'Etoille, 1986)
Paik ; Vostell ; Les Vasulka ; Viola ; Wegman ; Oursler, Tony ; Gautreau, Jean-Michel ; De Geetere, Patrick ; Cahen, Robert ; Bourges, Alain ; Theys, Koen ; Lafontaine, Marie-Jo ; Klier, Michaël ; etc.
Frans
boek